The Catholic peace tradition - Musto, Ronald G. (Peace Books, 2002)
This book is a history of the peace tradition in the Roman Catholic Church from the time of the Gospels to the twentieth century. Its purpose is to show that there is a continuing, unbroken, and self-sustaining stream within Catholicism from the martyrs and pacifists of the early church to John XXIII and the peacemakers of our time.-- Provided by publisher.